1979
DOI: 10.1115/1.3448974
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flow Over a Plane Symmetric Sudden Expansion

Abstract: Turbulent flow with separation and recirculation over a double backward facing step has been investigated experimentally. Time mean stream wise, transverse and cross-stream components of the velocity fluctuations, together with turbulence kinetic energy and Reynolds shear stresses, were measured using a laser Doppler anemometer, operating in the differential Doppler mode with forward scattering. Ordinary tap water was used in a closed loop flow system with a Reynolds number of 30,210 and significant changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The negative velocities inside the recirculation regions are overpredicted and there is a tendency for the calculated profiles to recover more rapidly in part due to the use of the law of the wall as confirmed by the recent DNS of Le et al [18] and the experiments of Jovic and Driver [25]. Further, the use of a two-layer model will not guarantee a better performance, since it has been reported that conflicting results have been obtained for backward-facing step flows by Chen and Patel [26] and Iacovides and Launder [27], who predicted the velocity profiles for a 1.125 expansion with a good accuracy, whereas for an expansion ratio of 1.5, Smyth [28] predicted a much stronger reverse flow than the experiments. Also, the results in the redevelopment region are sensitive to those obtained in the recirculation regions, where it is known that excessive diffusion in the shear layer is predicted by the present turbulence model.…”
Section: Calculationsmentioning
confidence: 99%
“…The negative velocities inside the recirculation regions are overpredicted and there is a tendency for the calculated profiles to recover more rapidly in part due to the use of the law of the wall as confirmed by the recent DNS of Le et al [18] and the experiments of Jovic and Driver [25]. Further, the use of a two-layer model will not guarantee a better performance, since it has been reported that conflicting results have been obtained for backward-facing step flows by Chen and Patel [26] and Iacovides and Launder [27], who predicted the velocity profiles for a 1.125 expansion with a good accuracy, whereas for an expansion ratio of 1.5, Smyth [28] predicted a much stronger reverse flow than the experiments. Also, the results in the redevelopment region are sensitive to those obtained in the recirculation regions, where it is known that excessive diffusion in the shear layer is predicted by the present turbulence model.…”
Section: Calculationsmentioning
confidence: 99%
“…Smyth 13 performed a comprehensive experimental study at Re= 20 140, but his measurements refer to an expansion ratio of 1.5 and a symmetric flow pattern. He found an approximately two-dimensional flow in the midplane of the channel, which seems reasonable in view of the high aspect ratio ͑A = 30.4͒ considered in his work.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, detailed quantitative information on this highly turbulent, reversing flow requires advanced velocity measurement techniques (such as laser Doppler anemometry), and the use of these techniques in sudden expansion flows has only begun in recent years. In recent years, laser Doppler anemometry (LDA) was used by Cherdron et al (1978) to study the axisymmetric sudden expansion, and by Smyth (1979) to investigate the plane, symmetric (double step) expansion. These studies provided information on the overall structure of the sudden expansion flow and helped identify various flow zones.…”
mentioning
confidence: 99%